1990
DOI: 10.1093/oxfordjournals.jbchem.a123127
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Discrimination of Intralysosomal, Cytosolic, and Two Membrane Sialidases Present in Rat Tissues1

Abstract: Cytosolic sialidase was purified from rat skeletal muscle, and the purified enzyme migrated as a single band of Mr 43,000 on sodium dodecyl sulfate-polyacrylamide gel electrophoresis. A polyclonal antibody raised against the enzyme inhibited and immunoprecipitated rat liver cytosolic sialidase as well as the muscle enzyme but failed to cross-react with the intralysosomal sialidase of rat liver and membrane sialidases I (synaptosomal) and II (lysosomal) of rat brain. The antibody against brain membrane sialidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…The concentration of released sialic acid was measured by phenobarbituric method [25]. The immunotitration results (Table 1) showed that antibodies raised against recombinant lysosomal sialidase precipitated all activity of lysosomal sialidase in human liver extract, but not of cytosolic or plasma membrane sialidases, thus confirming that the antibodies are specific against the lysosomal enzyme and that the lysosomal, plasma membrane and cytosolic sialidases do not have common antigenic determinants, as has been suggested [26]. The anti-sialidase antibodies did not precipitate purified GAL (not shown) but precipitated up to 8 % of GAL activity in liver extract, which probably represents the fraction of GAL associated with the lysosomal sialidase in the 1n27 MDa complex.…”
Section: Immunotitrationmentioning
confidence: 54%
“…The concentration of released sialic acid was measured by phenobarbituric method [25]. The immunotitration results (Table 1) showed that antibodies raised against recombinant lysosomal sialidase precipitated all activity of lysosomal sialidase in human liver extract, but not of cytosolic or plasma membrane sialidases, thus confirming that the antibodies are specific against the lysosomal enzyme and that the lysosomal, plasma membrane and cytosolic sialidases do not have common antigenic determinants, as has been suggested [26]. The anti-sialidase antibodies did not precipitate purified GAL (not shown) but precipitated up to 8 % of GAL activity in liver extract, which probably represents the fraction of GAL associated with the lysosomal sialidase in the 1n27 MDa complex.…”
Section: Immunotitrationmentioning
confidence: 54%
“…These developmental differences, together with property differences (for example the optimal pH) may be in favour of the concept [22,23] that the various…”
Section: Ultrastructural Analysismentioning
confidence: 99%
“…Sialidase is targeted to the endosomal-lysosomal compartment as an integral membrane protein by vesicular transport, which involves association of the adapter proteins with a tyrosine-containing internalization signal at the C-terminus of the enzyme [Lukong et al, 2001]. It is likely that the transmembrane domain in the lysosome is cleaved similarly to that of acid phosphatase, resulting in the appearance in the cell of two pools of lysosomal sialidase, soluble and membraneassociated, which are both absent in cultured cells of sialidosis patients [Verheijen et al, 1983;Miyagi et al, 1990Miyagi et al, , 1992Miyagi et al, , 1993. Immunoelectron microscopy demonstrated that, in addition to the lysosomal membrane and lysosomal lumen, NEU1 sialidase is present on the plasma membrane and in intracellular (possibly endocytic) vesicles [Vinogradova et al, 1998].…”
Section: Introductionmentioning
confidence: 99%